2010
DOI: 10.3324/haematol.2010.035162
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K1 supplementation to improve the stability of anticoagulation therapy with vitamin K antagonists: a dose-finding study

Abstract: BackgroundPoor anticoagulant stability in patients using vitamin K antagonists is a risk factor for both bleeding and thrombosis. In previous studies supplementation with low dose vitamin K1 was shown to improve the stability of anticoagulant control. We set up a study to confirm earlier reports and to determine the optimal daily dose of vitamin K1 in preparation of a large study with clinical endpoints. Design and MethodsFour hundred patients from two anticoagulation clinics starting with vitamin K antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 23 publications
0
61
0
Order By: Relevance
“…41 Three randomized, placebo-controlled trials using pharmaceutically prepared vitamin K have addressed this issue. [42][43][44] There are important differences among these RCTs, including the daily dose of vitamin K studied (100 m g, 42,44 150 m g, 43,44 or 200 m g 44 ), the study participants (general anticoagulation clinic patients 42,44 or patients with unstable INR control 43 ), the width of targeted INR range (1.5 42,44 or 1.0), and type of VKA (phenprocoumon or warfarin). Table 5 (and Table S5) shows the quality of evidence and main fi ndings of our meta-analysis of the three RCTs.…”
Section: Vitamin K Supplementationmentioning
confidence: 99%
“…41 Three randomized, placebo-controlled trials using pharmaceutically prepared vitamin K have addressed this issue. [42][43][44] There are important differences among these RCTs, including the daily dose of vitamin K studied (100 m g, 42,44 150 m g, 43,44 or 200 m g 44 ), the study participants (general anticoagulation clinic patients 42,44 or patients with unstable INR control 43 ), the width of targeted INR range (1.5 42,44 or 1.0), and type of VKA (phenprocoumon or warfarin). Table 5 (and Table S5) shows the quality of evidence and main fi ndings of our meta-analysis of the three RCTs.…”
Section: Vitamin K Supplementationmentioning
confidence: 99%
“…Table summarizes the findings of the individual studies. Of the three RCTs, only the Sconce et al () study demonstrated a significant clinical benefit with TTR increasing, on average, by 28% for those receiving vitamin K. Both Rombouts et al () and Gebuis et al () saw an increase in TTR for subjects receiving vitamin K compared to placebo in all dosing groups, but these findings did not achieve statistical significance. Differences between groups regarding other outcome measures were identified.…”
Section: Resultsmentioning
confidence: 96%
“…The majority of included studies used a randomized controlled design (Gebuis et al, ; Rombouts et al, ; Sconce et al, ). Sconce et al () randomized 70 patients with unstable INRs unrelated to poor adherence on warfarin treatment for atrial fibrillation to either 150 μg of vitamin K or placebo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Ingesting a consistently high amount of vitamin K-containing food is challenging for many patients, thus supplementing the diet with pharmaceutically prepared vitamin K has been explored as a means to improve INR control in three RCTs. [31][32][33] When results of these trials were pooled, the absolute improvement in TTR was 3.54% (95% CI, 1.13-5.96%). Unfortunately, these trials mostly enrolled patients with already stable INR control and therefore failed to address the more relevant issue of whether daily vitamin K supplementation would improve INR control in patients with unstable INRs not due to other correctable factors.…”
Section: Vitamin K Intakementioning
confidence: 95%